Profitability as a Moderator of GCG and CSR Effects on Company Value with Company Size Controls on IDX - Dettha Restya Utami; Gunarianto; Ana Sopanah (Optima Science, 2025)
The purpose of this study is to test and explain the effect of good corporate governance and corporate social responsibility on company value with profitability as a moderating variable and company size as a control variable. The population in this study were all food and beverage sub-sector companies listed on the Indonesia Stock Exchange in 2021-2023, totaling 26 companies. In this study, the sampling method used purposive sampling technique or based on certain criteria. Inferential analysis in this study used SmartPLS software version 4 which started from model measurement (outer model), model structure (inner model) and hypothesis testing (bootstrapping). The results of the study showed that there was a control variable, GCG had a significant effect on company value. However, when the control variable, namely company size, was included in the research model, GCG did not have a significant effect on company value. CSR did not have a significant effect on company value. Likewise, when the control variable was included in the research model, CSR also did not have a significant effect on company value. Thus, company size does not affect the effect of CSR on company value. Before the control variable, profitability had a significant effect on company value. Likewise, when the control variable is included in the research model, profitability also has a significant effect on company value. Profitability is able to play a role in moderating all the effects of GCG on company value. The moderating effect of profitability on the effect of GCG on company value has a large effect with a weakening nature. Profitability is able to play a role in moderating all the effects of CSR on company value. The moderating effect of profitability on the effect of GCG on company value has a large effect with a strengthening nature. company size acts as a control variable for the effect of good corporate governance and social responsibility on company value.